Strategi Pengembangan Obyek Wisata Bukit Matang Kaladan Terhadap Pendapatan Asli Desa Tiwingan Lama Kabupaten Banjar - Nurahman Hadadi; Muzdalifah Muzdalifah (PPJP Universitas Lambung Mangkurat, 2022)
This study aims to (1) develop strategies that need to be carried out in developing Bukit Matang Kaladan Tourism Object, (2) know the contribution of Bukit Matang Kaladan Tourism Object to the village's original income, and (3) know the role of government in developing Bukit Matang Tourism Object Kaladan. Respondents in this study were six respondents who were considered influential and experts. They knew the tourism situation, especially in Banjar District, which was used in data processing using the SWOT method. This study provides the results of developing the strategy that best suits the situation is the SO strategy (1) With the superiority of the landscape and maintaining a conducive tourist environment; tourists will continue to visit these attractions, plus a strategic location. (2) Maximizing the role of POKDARWIS and training provided by the Banjar Regency Culture and Tourism Office to promote tourism objects with the opportunities that are already available.